In Silico Study of Compounds Contained in Hemigraphis alternata Leaves against 5-LOX for Anti-Inflammatory - Yeni Yeni; Rizky Rachmania; Mochamad D. Yanuar (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Inflammation is a self-protection response to begin the healing process. One of the anti-inflammatory targets worth developing is lipoxygenase inhibitors, which have been studied for several diseases, including severe airways disease. The aim of this study was to predict the affinity of 23 compounds that contained in Hemigraphis alternata leaves against 5-lipoxygenase (5-LOX). The compounds of Hemigraphis alternata leaves were screened for its affinity againts 5-LOX using docking software, DOCK 6.9, with zileuton as the comparator. Based on the grid score, most of the 23 of Hemigraphis alternata leaves compounds showed a higher affinity towards 5-LOX compare to zileuton. The highest affinity was shown by n-hexadecanoid acid. The study showed that Hemigraphis alternata leaves contains potential active components that could be developed as 5-LOX-inhibitor.Keywords: In silico, Hemigraphis alternata, lipoxygenase, anti-inflammatory